Pressão positiva expiratória e parâmetros da função pulmonar em pacientes com fibrose cística - Sandra Ribeiro Pires (2007)
Cystic Fibrosis is a potential lethal genetic disease common in the Caucasian race. Disease initiates with a dysfunction in the respiratory epithelium that leads to thickened mucus, inflammation and chronic infection in the airway. The airway clearance techniques are an important component in the treatment of the patient with Cystic Fibrosis, and should be considered a routine. There are several clearance techniques and some of them incentive patients independence. Positive expiratory pressure increases mouth pressure, which, in turn, is transmitted to the airways, maintaining them open during expiration, preventing their collapse and, thus, reducing air trapping in the lungs. Instrumental resources, such as Flutter® and EPAP (expiratory positive airway pressure) have been used to remove secretions and increase the pulmonary ventilation in patients with Cystic Fibrosis. However, there are few studies on the immediate effects of EPAP, a resource with advantages such as independence of the position of the device to generate positive pressure, the possibility of giving a pre-determined pressure value in the airways and low cost. Thus, the aim of this study was to evaluate some pulmonary function parameters, mainly functional residual capacity and residual volume, after the use of two types of positive expiratory pressure (EPAP and Flutter®) in patients with Cystic Fibrosis. Thirteen patients with Cystic Fibrosis, 8 men and 5 women, aged 18,54 (± 3,23) years and with a Body Mass Index of 20,13 (±3,15)Kg/m2, with spirometry ranging from normal to moderate dysfunction, participated in the study. The patients used EPAP with a resistance of 15 cmH2O and Flutter® in a randomized way, during 15 minutes, with a one-week interval. The single-breath helium test was used to measure the functional residual capacity, residual volume (RV), total lung capacity (TLC) and to calculate the RV/TLC ratio. Spirometry was used to measure forced vital capacity (FVC), forced expiratory volume in one second (FEV1), forced expiratory flow between 25% and 75% of FVC and the FEV1/FVC ratio. Pulmonary function tests were realized before and 15 minutes after the physiotherapy session. Arterial oxyhemoglobin saturation was measured before, during and after treatments. The number of coughs and the patients device preference were registered. A two-way ANOVA was used in the statistical analysis, and p<0,05 was considered significant. No significant changes in any of the analyzed variables, in the different comparisons, were observed. Coughs were observed in 3 patients who presented the worst pulmonary function. Of the 13 patients who participated in the study, 6 preferred EPAP, 4 preferred Flutter® and 3 didnt relate a preferred device. In conclusion, the use of EPAP and Flutter® didnt lead to significant changes, in a short term period, in the pulmonary function of teenage and adult patients with Cystic Fibrosis.